09 Can older people who fall be identified in the ambulance call centre to enable alternative responses or care pathways?. Issue 3 (1st March 2011) - Snooks, Helen; Cheung, Wai Yee; Gwini, Stella May; Humphreys, Ioan; Sánchez, Antonio; Siriwardena, Niroshan
Abstract : Background: Older people who fall make up a substantial proportion of the 999 workload. They are a particularly vulnerable group who may benefit from referral to specialised community based falls services. This requires early identification, ideally from dispatch codes assigned in the ambulance call centre. Objective: To assess the feasibility of using information given during 999 calls to identify older people who fall and who may benefit from an alternative response. Methods: We examined all records of patients aged 65 years and over during 2008 in the Nottinghamshire area and identified those recorded as having fallen by attending crews. Dispatch codes were recorded for all cases and the utility of the dispatch code 'Fall without priority symptoms' (AMPDS 17) for identifying older people who had fallen was assessed. Results: From 56 584 emergency (999) calls recorded, including 8119 for patients aged 65 years and over, 3246 (40%) cases were recorded as a fall. Of these, 2186 (67%) had been allocated AMPDS code 17 at dispatch (true positives), and 413 (13%) had not (false negatives), with 647 unknowns. Of 4871 cases not categorised as a fall by attending crews, 175 (4%) had been allocated an AMPDS code 17 (false positives), and 3315 (68%) had been given other codes (true negatives), with 1381 unknowns. The dispatch code AMPDS 17 had a sensitivity of 84% and a specificity of 95% for identifying falls compared with categorisation by crews. Limitations: Definition of a fall is not always clear and there may be variations in usage of the category by crews. There was a high level of missing data in this study. Conclusion: A large majority of older people who fall and for whom a 999 call is made can be identified in the ambulance call centre using dispatch codes. This provides a means for rapid and effective targeting of alternative responses to these patients, thereby potentially improving processes and outcomes of care.